The extraction of polycyclic aromatic hydrocarbons from water samples with aromatic-dithiocarbamate modified magnetic nanoparticles - Ma, Yurong (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
Considering the urgent need for the analysis of trace-level pollutants in water samples, the pre-concentration of micropollutants in water samples has been the focus of extensive research. Among current pretreatment methods, the solid phase extraction (SPE) technique has received enormous attention because of its low cost, ease of operation and high efficiency. In this work, a new adsorbent (Fe3O4Au@DTC NPs) was acquired through modification of Fe3O4 nanoparticles (NPs) with gold (Au) and dithiocarbamate (DTC). To investigate their application ability, the adsorbent were utilized as an SPE adsorbent to enrich polycyclic aromatic hydrocarbons in water (PAHs, fluoranthene, pyrene, benzo anthracene, benzo fluoranthene, benzo pyrene). The obtained Fe3O4@Au@DTC NPs were confirmed by transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), vibrating sample magnetometer (VSM), and UV-Vis spectrum. Under optimal conditions, the calibration curves were obtained in the range of 10-500 ng L-1, while the limit of detection (LOD) ranged in 1.17-2.31 ng L-1. Furthermore, 50 mg of Fe3O4@Au@DTC NPs could extract trace PAHs from 500 mL real water samples into 1 mL eluent, and the spiked recoveries of five PAHs in river water and tap water reached 72-106% with relative standard deviations varying between 3.3-5.18%. Through the conversion of amines into DTC, we acquire desiring group modified Fe3O4 NPs, which showed great prospects in magnetic solid-phase extraction sphere and environmental field